2015
DOI: 10.1007/164_2015_36
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-Dependent Protein Kinase and cGMP-Dependent Protein Kinase as Cyclic Nucleotide Effectors

Abstract: The cAMP-dependent protein kinase (PKA) and the cGMP-dependent protein kinase (PKG) are homologous enzymes with different binding and activation specificities for cyclic nucleotides. Both enzymes harbor conserved cyclic nucleotide-binding (CNB) domains. Differences in amino acid composition of these CNB domains mediate cyclic nucleotide selectivity in PKA and PKG, respectively. Recently, the presence of the noncanonical cyclic nucleotides cCMP and cUMP in eukaryotic cells has been proven, while the existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 80 publications
2
23
0
Order By: Relevance
“…In addition, we found that several other SNF1‐subfamily protein kinases can also target the regulated phosphorylation sites in vitro (Figure 8). Consistent with the fourth possibility, cGMP‐activated kinases (Protein Kinase G) have been shown to be activated by high levels of cAMP, similar to those measured in PKA‐null cells in the present study 32,33 . Prior studies have found that AMPK can be activated by nitric oxide working through cGMP 34,35 pointing to a role for Protein Kinase G in the regulation of AMPK.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we found that several other SNF1‐subfamily protein kinases can also target the regulated phosphorylation sites in vitro (Figure 8). Consistent with the fourth possibility, cGMP‐activated kinases (Protein Kinase G) have been shown to be activated by high levels of cAMP, similar to those measured in PKA‐null cells in the present study 32,33 . Prior studies have found that AMPK can be activated by nitric oxide working through cGMP 34,35 pointing to a role for Protein Kinase G in the regulation of AMPK.…”
Section: Discussionsupporting
confidence: 89%
“…However, as cAMP binding to PKA RIα is highly cooperative, cyclic nucleotide binding to the full-length protein and the isolated CNB domains cannot be directly compared [43]. Previous studies on isolated CNB domains of PKA RIα showed that CNB-B is more selective for cAMP compared with CNB-A [41,44]. In agreement with former studies, the selectivity of the isolated CNB-B remains the same as for CNB-B in the full-length PKA RIα [42].…”
Section: Resultsmentioning
confidence: 99%
“…Three PKG isoforms have been identified (PKG-type Iα (PKG Iα), PKG-type Iβ (PKG Iβ), and PKG-type II (PKG II)), whereby PKG Iα and PKG Iβ are splice variants originating from alternative splicing of one single gene. In the cardiovascular system, PKG I is the major isoform—PKG Iα and PKG Iβ are expressed in VSMCs—while ECs express PKG Iβ, and CMs express PKG Iα [ 1 , 26 , 46 , 47 , 48 , 49 , 50 ]. Second, cyclic nucleotide-gated (CNG) channels, nonselective cation channels, can be activated by the binding of cGMP or cyclic adenosine 3′,5′-monophosphate (cAMP).…”
Section: Cgmp Signaling In the Cardiovascular Systemmentioning
confidence: 99%